Enhanced in-situ sludge reduction of the side-stream process via employing micro-aerobic approach in both mainstream and side-stream. (June 2023) - Peng, Si-Mai; Luo, Hai-Chao; Wang, Zi-Han; Yang, Shan-Shan; Guo, Wan-Qian; Ren, Nan-Qi
Highlights: Micro-aerobic enhanced SRE of short HRT side-stream process significantly. AAMOM4 achieved 30.41% SRE and maintained carbon and nitrogen removal efficiency. Micro-aerobic in MSR accelerated the hydrolysis of POM and promoted denitrification. Micro-aerobic in SSR increased cell lysis and ATP dissipation. Hydrolytic, slow growing, predatory and fermentation bacteria cooperated to raise SRE. Abstract: Side-stream reactor (SSR), as an in-situ sludge reduction process with high sludge reduction efficiency (SRE) and less negative impact on effluent, has been widely researched. In order to reduce cost and promote large-scale application, the anaerobic/anoxic/micro-aerobic/oxic bioreactor coupled with micro-aerobic SSR (AAMOM) was used to investigate nutrient removal and SRE under short hydraulic retention time (HRT) of SSR. When HRT of SSR was 4 h, AAMOM system achieved 30.41% SRE, while maintaining carbon and nitrogen removal efficiency. Micro-aerobic in mainstream accelerated the hydrolysis of particulate organic matter (POM) and promoted denitrification. Micro-aerobic in side-stream increased cell lysis and ATP dissipation, thus increasing SRE. Microbial community structure indicated that the cooperative interactions among hydrolytic, slow growing, predatory and fermentation bacteria played key roles in improving SRE. This study confirmed that SSR coupled micro-aerobic was a promising and practical process, which could benefit nitrogen removal and sludge reduction in municipal wastewater treatment plants.